2003
DOI: 10.1037/h0088874
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive doll play: Helping children cope with change.

Abstract: Play therapists working with young children utilize a variety of developmentally appropriate methods in order to help children cope with unpredictable events. Although widely researched but lacking in generalized findings, one approach commonly used by therapists is doll play. A case study was conducted using five sessions of adaptive doll play with a five-year-old child experiencing separation anxiety. Clinging behaviors, crying, and requests by the child to call home to the parent while at school were all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…If left untreated, these problems can lead to more serious and costly problems in adolescence (U.S. Public Health Service, 2000). Other controlled play therapy outcome studies, conducted with primarily Caucasian children, have shown moderate to large treatment effects on internalizing problems when play therapy was compared to no treatment (Brandt, 1999;Constantino et al, 1986;Jones et al, 2002;Packman & Bratton, 2003); while other play therapy studies have reported less favorable results on internalizing behaviors (Rennie, 2000;McGuire, 2001;Danger, 2003).…”
Section: Internalizing Problemsmentioning
confidence: 99%
“…If left untreated, these problems can lead to more serious and costly problems in adolescence (U.S. Public Health Service, 2000). Other controlled play therapy outcome studies, conducted with primarily Caucasian children, have shown moderate to large treatment effects on internalizing problems when play therapy was compared to no treatment (Brandt, 1999;Constantino et al, 1986;Jones et al, 2002;Packman & Bratton, 2003); while other play therapy studies have reported less favorable results on internalizing behaviors (Rennie, 2000;McGuire, 2001;Danger, 2003).…”
Section: Internalizing Problemsmentioning
confidence: 99%
“…The other six articles were identified by the authors as case studies but were not presented as research case studies, and instead they might best be termed practitioner-based narratives of an interesting case (Danger, 2003;De Domenico, 2002;Snow et al, 2004;.…”
Section: Results Describedmentioning
confidence: 99%
“…Therapy with dolls has a long tradition and is often used to assist children in coping with and managing change. "Adaptive doll play" is a play therapy technique that "has been focused on dramatizing specific anxiety-producing events, wherein concrete demonstrations lead to a decrease in fear" (Danger, 2003). Of course, we know that children, and some adults, play with dolls on their own and with friends, without a psychotherapist present, to do similar kinds of processing.…”
Section: Trans Patients In Second Lifementioning
confidence: 99%